CosMAC: Constellation-Aware Medium Access and Scheuduling for IoT Satellites - Shenoy, Jayanth; Chabra, Om; Chakraborty, Tusher; Jog, Suraj; Vasisth, Deepak; Chandra, Ranveer (ACM MobiCom, 2024)
Pico-satellite (picosat) constellations aim to become the defacto connectivity solution for Internet of Things (IoT) devices. These constellations rely on a large number of small picosats and offer global plug-and-play connectivity at low data rates, without the need for Earth-based gateways. As picosat constellations scale, they run into new bottlenecks due to their traditional medium access designs optimized for single (or few) satellite operation. We present CosMAC – a new constellation-aware medium access and scheduling system for picosat networks. CosMAC includes a new overlap-aware medium access approach for uplink from IoT to picosats and a new network layer that schedules downlink traffic from satellites. We empirically evaluate CosMAC using measurements from three picosats and large scale trace-driven simulations for a 173 picosat network supporting 100k devices. Our results demonstrate that CosMAC can improve the over-all network throughput by 6.5× over prior state-of-the-art satellite medium access schemes.